Pengaruh promosi penjualan terhadap minat pembeli dalam kegiatan Bazar Maliki Fest - Dewi, Dinda Ruliana (Maliki Interdisciplinary Journal, 2023)
This research uses a quantitative method where the author makes direct observations regarding the influence of sales promotions on buyer interest in Maliki Fest activities which were held at UIN Maulana Malik Ibrahim Malang. The objects of this research are all UIN Maliki Malang students on campus. The research results show that there is an influence of sales product promotions which can influence students’ interest in buying products being sold. How sellers promote products to get customers to buy the product. Simultaneously, promotions can have an influence on consumer purchasing decisions at the Kedai Kita Maliki Fest bazar.